KEBERADAAN PANTI JOMPO DALAM MASYARAKAT DAN BUDAYA ACEH (SUATU ANALISIS SOSIOLOGIS) - Irma Juraida (Jurnal Community, 2018)
Abstract      This study discusses how the existence of the Jambo Home in the Society and Culture of Aceh is known to be religious and cultured . In the Acehnese society and culture itself, children still feel obligated and have loyalty to abandon their parents who can not take care of themselves. Values and culture prevailing in society, children are obliged to give affection to their parents .. The problem in this research is how the existence of Panti Jompo in Aceh society culture. This study uses a qualitative approach, mainly through in-depth interview techniques with face-to-face and observation. This paper aims to explore the understanding of a habit, the socio-religious and cultural values of the people of Aceh towards Janti Jompo.The results of this study indicate that the Nursing Home in the culture of the people of Aceh is more determined by the interaction (knowledge) of social background, culture and religious values which is shared by a person or group in Aceh society.Key Words: Nursing Home, Culture, People of Aceh